Advancing Educational Equity Research, Policy, and Practice - Kristen Campbell Wilcox; Hal A. Lawson (MDPI AG, 2022)
As student populations worldwide become more diverse and many are challenged by poverty and social exclusion, educational equity's importance grows, both as a core value and as a driver for school improvement and redesign. While national and local policies vary, as do resources in support of equity outcomes, it is timely to identify, synthesize, and evaluate the available research with special attention to commonalities, similarities, and lessons learned. Mindful of selectivity, we summarize eighteen years' worth of equity-focused research and development conducted under the sponsorship of a state-funded initiative in the USA called NYKids. Utilizing practice-embedded research methodologies, research teams have identified, described, and interpreted seven keynote features of equity-oriented schools. They also have implemented research-practice partnerships that facilitate equity-oriented school improvement. This holistic, evidence-based, and practice-centered approach can be classified as "a strong equity approach", albeit a selective one, when alternatives worldwide are surveyed.